Medical treatment of an unusual cerebral hydatid disease - Shu Chen; Ning Li; Feifei Yang; Jiqin Wu; Yuekai Hu; Shenglei Yu; Qi Chen; Xuan Wang; Xinyu Wang; Yuanyuan Liu; Jianming Zheng (BMC Infectious Diseases, 2018)
Abstract Background Hydatid disease is a worldwide zoonosis produced by the larval stage of cestodes of the Echinococcus genus. Hydatid disease primarily involves the liver and lungs. The brain is involved in less than 2% of cases. Surgery has long been the only choice for the treatment, but chemotherapy has been successfully replaced surgery in some special cases. Case presentation We report a rare hydatid disease case which presented with multiple lesions in right frontal lobe, an uncommon site, and in the liver and lungs. A 28-year-old woman presented with 6 months history of recurrent convulsion. Cranial magnetic resonance imaging found multiple lesions in right frontal lobe, so she was hospitalized for surgical treatment and received sodium valproate by oral for controlling epilepsy. Before the operation, other lesions were found in the liver and lungs by computerized tomography scan. There were multiple pulmonary nodules near the pleura and large cyst in the liver. The pathology of liver showed that it may be a hydatid disease. Then, positive serum antibodies for echinococcus antigen further confirmed our diagnosis. Since her central nerve system was involved, she received four pills (800 mg, about 17 mg/kg/day) albendazole treatment for 18 months without operation. Her symptoms abated and a follow-up magnetic resonance imaging showed that the lesion had obviously diminished after treatment. She was recurrence free 2 years after we stopped albendazole treatment. Conclusions This case reveals an uncommon pattern of intracranial hydatid disease. Albendazole can be beneficial for some inoperable cerebral hydatid disease patients.